High-charge divergent electron beam generation from high-intensity laser interaction with a gas-cluster target. (27th April 2015) - Koester, P.; Bussolino, G.C.; Cristoforetti, G.; Faenov, A.; Giulietti, A.; Giulietti, D.; Labate, L.; Levato, T.; Pikuz, T.; Gizzi, L.A.
Abstract We report on an experimental study on the interaction of a high-contrast 40 fs duration 2 TW laser pulse with an argon-cluster target. A high-charge, homogeneous, large divergence electron beam with moderate kinetic energy (~2 MeV) is observed in the forward direction. The results show that an electron beam with a charge as high as 12 nC can be obtained using a table-top laser system. It was demonstrated that the accelerated electron beam is suitable for a variety of applications such as micro-radiography of thin samples in a wide field of view. It can also be applied for in vitro dosimetry studies.